Accountability Analysis of Village Financial Management in Sipaenre Village, Kindang District, Bulukumba District - Nimra; Sahade; Idrus, Mukhammad (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to determine the accountability of village financial management in Sipaenre Village, Kindang District, Bulukumba Regency. The variable in this research is the accountability of village financial management in Sipaenre Village. The population in this research is Village Officials, Village Financial Data and Documents from Sipaenre Village, Kindang District, Bulukumba Regency. The sample in this research is the Village Head. Village secretary. Village Treasurer, Community figure. Village Financial Data and Documents related to the problem studied. Data collection techniques use interviews and documentation. The data analysis technique uses qualitative descriptive analysis. The results of this research indicate that village financial management in Sipaenre Village, Kindang District, Bulukumba Regency is quite in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management.